Study to Review Benefits Beyond Direct Mine Taxes in Zambia - *, G. Mwamba; Kambani, S.; Chisakulo, E. (IJRDO - Journal of Business Management, 2017)
There is a common public perception that the major contribution of mining in Zambia is through direct tax revenues. This study sought to explore and investigate the economic benefits of mining beyond these direct tax revenues. Over seventy percent (70%) of Zambia’s copper production is by four mining companies namely Barrick Lumwana Mines, First Quantum Minerals (FQM) Kansanshi mine, Konkola Copper Mine (KCM) and Mopani Copper. These mines were the focus of this study. The objectives of the study were to determine how much they paid in terms of taxes; employment created; investments made in terms of procurement of local goods and services; assessment of the social benefits from the four mining companies and other macroeconomic benefits of mining in Zambia. And finally, to compare mine tax revenue to other benefits of mining in Zambia and determine which of the two is greater. Using data collected from the four mining companies, Zambia Chamber of Mines, Zambia Revenue Authority and Action Aid, the findings were that the four mining giants during the period of investigation, made immense contributions to the country’s economy. In 2012, they directly employed 56,300 people, spent about US3.0 billion on the procurement of goods and services and US70 million on social investments. However, these companies spent about only US1.7 billion in form of total taxes. This study has therefore, demonstrated that the four mining companies comparatively generated significant economic benefits to the country outweighing the taxes paid in three areas of employment, procurement of goods and services and social investments. Clearly, the findings from this research do not support the common perception that the payment of taxes is the main and most important benefit derived from the mining activities in Zambia. The study concludes that tax revenue is but a small benefit of mining in Zambia. There are significant benefits in terms of support for local business, social investments and other macro-economic benefits that needs strengthening through appropriate policy interventions. Being a mineral dependent economy, this conclusion is not meant to demean the desire by the government to have more direct tax revenues to pay for other equally demanding sectors of the national economy but to create awareness that other important benefits do accrue to the country other than direct taxes